2019 IEEE International Conference on Image Processing (ICIP) 2019
DOI: 10.1109/icip.2019.8803607
|View full text |Cite
|
Sign up to set email alerts
|

VisionISP: Repurposing the Image Signal Processor for Computer Vision Applications

Abstract: Traditional image signal processors (ISPs) are primarily designed and optimized to improve the image quality perceived by humans. However, optimal perceptual image quality does not always translate into optimal performance for computer vision applications. We propose a set of methods, which we collectively call VisionISP, to repurpose the ISP for machine consumption. VisionISP significantly reduces data transmission needs by reducing the bit-depth and resolution while preserving the relevant information. The b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…ISP has the information that can explain the image variation and computer vision can learn to compensate through that variation. Through this, computer vision can complement the function of ISP and if the function of ISP is used for low-level operations such as denosing, and computer vision is used for high-level operation; this can secure capacity and lower processing power [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…ISP has the information that can explain the image variation and computer vision can learn to compensate through that variation. Through this, computer vision can complement the function of ISP and if the function of ISP is used for low-level operations such as denosing, and computer vision is used for high-level operation; this can secure capacity and lower processing power [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…They train with simulated RAW images. Wu et al [17] suggested VisionISP, a trainable ISP, which is trained to optimize object detection in an autonomous driving setting. In this work, instead of designing or training an image processing module, i.e., a module whose input and output are images, we are focused on the case that the vision model is operating on RAW images.…”
Section: Related Workmentioning
confidence: 99%
“…This happens because the ISP serves as a 'normalization' of the data, transforming it to a canonical space, which is independent (or less dependent) of the camera used or capturing environment. Solutions discussed in the literature usually involve an adjustment of the ISP for the vision task, either manually [18] or via learning [17]. Our method deals with the case where the ISP is discarded and mitigates the drop in performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently even standard image signal processing (ISP) chips include neural co-processors and, of course, many companies are developing increasingly advanced chips. At the time of this writing neural image analysis is increasingly a standard component camera component, especially in mobile devices [83,84] and proposals have emerged for ISP chips designed specifically for neural processing [85,86].…”
Section: Cameras and Artificial Neural Networkmentioning
confidence: 99%

Smart Cameras

Brady,
Hu,
Wang
et al. 2020
Preprint